Constructing Carbon Nanotube Hybrid Fiber Electrodes with Unique Hierarchical Microcrack Structure for High‐Voltage, Ultrahigh‐Rate, and Ultralong‐Life Flexible Aqueous Zinc Batteries. Issue 11 (20th December 2022) - Wang, Hui; Lu, Yufei; Nie, Zhentao; Liu, Haodong; Dai, Bingfei; Shi, Xiaofan; Yan, Bing; Zhao, Tiancheng; Zhang, Zhitao; Zhu, Jixin; Zhao, Yang
Abstract: Flexible aqueous zinc batteries are promising candidates as safe power sources for fast‐growing portable and wearable electronics. However, the low working voltage, poor rate capability, and cycling stability have greatly restricted their development and applications. Here, a new family of flexible bimetallic phosphide/carbon nanotube hybrid fiber electrodes with unique macroscopic microcrack structure and microscopic porous nanoflower structure is reported. The hierarchical microcrack structure not only facilitates the penetration of electrolyte for effective exposure of active sites, but also can serve as buffers to relieve the stress concentrations of the fiber electrode under deformations, enabling impressive electrochemical performance and mechanical flexibility. Particularly, the fabricated flexible aqueous zinc batteries demonstrate high working voltage plateau and specific capacity (≈1.7 V, 258.9 mAh g −1 at 2 A g −1 ), ultrahigh rate capability (135.8 mAh g −1 at 50 A g −1, fully charged in only 9.8 s) and impressive power density of 79 000 W kg −1 . Moreover, the flexible batteries show ultralong cycling life with 74.6% capacity retention after 20 000 cycles. The fiber batteries are also highly flexible and can be easily knitted into soft electronic textiles to power a smartphone, which are particularly promising for the next‐generation of flexible and wearable electronics. Abstract : A new family of high‐performance flexible hybrid fiber electrodes with unique hierarchical microcrack structure is created. The assembled flexible aqueous zinc batteries exhibit high voltage plateau and specific capacity, ultrahigh rate capability, ultralong cycle life and superior flexibility, which can be easily knitted into soft electronic textiles to power a smartphone.